The Jubilee Year of Shanghai Cooperation Organization - V. Vorobiev (Международная аналитика, 2015)
The author contemplates about the prospects of SCO development according to the strategy formulated at the Ufa-2015 summit and its possible conjugation of this strategy with Chinese initiative of Silk Road. The stages of China global policy and the most recent shifts as compared with the political attitudes of Deng Xiaoping era are described.